The effects of presentation rate on semantic, syntactic, and orthographic processing and relationship to reading fluency in children - Wolfe, Donna L. (East Carolina University, 2011)
Reading fluency is the connection between reading decoding and reading comprehension. A child becomes fluent between second and third grade (Coltheart, 1978). However, it is unknown if fluency is strictly the result of rapid decoding or underlying language skills. It also is unknown how recognition of orthographic word forms, decoding rate, and accuracy independently contribute to the development of reading fluency. Broad relationships have been suggested between reading and oral language skills but studies are limited relative to the relationship between the development of reading fluency and underlying oral language abilities. Several studies have shown that semantic and syntactic abilities of oral language are related to later reading decoding and comprehension skills (Magnusson & Naucler, 1990; Menyuk et al., 1991). While relationships between these oral language abilities and later reading skills have been recognized to some degree, these studies are inconclusive regarding the relationship to reading fluency.   The purpose of the present investigation was to determine if semantic, syntactic, and orthographic processing abilities, as measured by reaction time and accuracy, are differentially affected as a function of stimulus modality (reading and auditory) and stimulus presentation rate. Participants included 50 second and third grade children (7 to 10 years of age) with varying reading and language skills based on a series of pre-experimental tasks. Participants completed a series of semantic, syntactic, and orthographic processing tasks within two controlled stimulus presentation durations for auditory and visual modalities. Relationships to pre-experimental reading and oral language tasks were explored.   Results from the reading tasks did not reveal an overall significant difference in mean reaction time between the semantic and syntactic decision reading tasks as a function of two presentation durations. However, children were more accurate in their ability to make semantic and syntactic decisions in the reading task for the longer presentation duration (1200 ms) than the shorter presentation duration (600 ms). Overall accuracy was higher for the semantic decision task than the syntactic decision task.   Results suggest that making judgments about oral language while using rapid decoding skills requires more information processing for children in this age group than a task that requires answering multiple choice questions. Semantic processing could be the main factor in overall reading efficiency that is not taken into account in current tests that measure reading fluency.   For the auditory linguistic tasks, children were able to make decisions about correctness faster for the syntactic decision than the semantic decision in the normal speech rate condition and the time-compressed speech rate condition. However, reaction time decreased for both tasks with time-compressed speech. Overall, children were more accurate in the normal speech rate condition than the time-compressed speech rate condition for both semantic and syntactic decisions. However, accuracy decreased for the semantic and syntactic decision in the auditory linguistic task when stimuli were presented in the time-compressed speech condition.  The current study suggests that there is a difference in processing content versus form (grammar) in reading tasks but not auditory tasks for children who are beginning fluent readers, suggesting that for beginning fluent readers, decreased accuracy in syntactic processing could be related to reading fluency rather than just language processing or the task itself.   There was no significant difference in reaction time between presentation duration conditions for an orthographic decision in a reading task. Accuracy increased for the orthographic decision in a reading task in general and the phonetic word type in particular for the shorter presentation duration (150 ms).   When making orthographic decisions in an auditory linguistic task, children were able to make decisions about spelling correctness faster for the time-compressed - 100 ms condition in comparison to the normal speech rate - 150 ms condition. Accuracy increased for the orthographic decision in general and the phonetic words in particular for the time-compressed speech condition.   Current results show that children can quickly and accurately determine if a word is spelled correctly between second and third grade when decoding skills are mastered and word recognition automaticity develops suggesting that orthographic verification and decoding skills are highly related skills (Hagiliassis, et al., 2006). For beginning fluent readers with varying reading skills, even the poorer readers may have less difficulty making discriminations for the phonetic word type than the nonphonetic word type.   The current study revealed that there was a strong relationship between oral language and reading fluency. Results suggest that rate of processing and stimulus duration may be factors in the overall assessment of efficient reading fluency. Results from the current study revealed that reading also involves making semantic and syntactic connections. The current study suggests that orthographic processing skills in the reading and auditory modality is an additional predictor of fluency single word identification (Burt, 2006). The current study also shows that for beginning fluent readers, there is more relationship between the rate of decoding and encoding spelling as seen in the orthographic decision or verification task, but semantic processing is still underdeveloped.
Keywords: Reading instruction; Language, General; Children; Fluency; Processing; Rate; Reading; Language; Comprehension; Semantics; Communication